PENGARUH KUALITAS SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI DAN PENYAJIAN LAPORAN KEUANGAN TERHADAP AKUNTABILITAS BADAN PUSAT STATISTIK PROVINSI PAPUA - Manur Sitinjak; Yundi Hafizrianda; Meinarni Asnawi (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2019)
The purpose of this study is to test and analyze the effect of Quality of HR, Technology Utilization and Exposure of Financial Reports for Accountability. The population of this discussion was all 68 respondents. Tests carried out on a sample of 68 respondents. The sampling method used is the Census. Information collection is done by direct survey. Testing the hypothesis is tested empirically using Path Analysis. The results showed that the Quality of Human Resources, Use of Information Technology and Presentation of Financial Statements had a positive and significant influence on Accountability. This means that if the Quality of Human Resources increases or gets better, Accountability will also be better. The use of Information Technology has proven to have a positive but not significant effect on Accountability. Furthermore, the presentation of financial statements proved to have a positive and meaningful effect on accountability. This shows that the quality of human resources, utilization of information technology, exposure to financial reports and accountability in the BPS of the Papua Province has been going well.